Penghijauan dan Pemanfaatan Lahan Sempit Guna Membangun Kesadaran Masyarakat Dalam Menjaga Lingkungan di Sekitar Sungai Sukodono, Desa Sambungrejo - Auliyaur Rabbani; Maharani Retno Budianti (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
A healthy and well-maintained environment is a shared responsibility. However, problems often occur in the environment because many people do not care. Especially in the upstream part of the river which is always used as a place for laying the results of river backfill every year. Another problem is the narrow area due to the dense population of the area. Narrow land occurs everywhere, not familiar with urban areas or semi-urban villages. In carrying out community service activities, the service team uses the following activity methods: 1. Observation 2. Project planning 3. Evaluation and sharing. In connection with the problem of narrow land, the actions of the branch management and the community around Aisiyah Sukodono Kindergarten affected the success of reforestation carried out by the KKN team. All forms of involvement, efforts, and roles starting from design, implementation and maintenance are real actions in making the surrounding environment more productive. In establishing self-reliance, it is necessary to cooperate with the branch management and the local village government to develop a productive yard culture on limited land. It is hoped that this reforestation can be done by planting plants and plants that support the basic ingredients of the surrounding community.